Where have all the beetles gone? Long‐term study reveals carabid species decline in a nature reserve in Northern Germany. Issue 4 (1st April 2019) - Homburg, Katharina; Drees, Claudia; Boutaud, Estève; Nolte, Dorothea; Schuett, Wiebke; Zumstein, Pascale; von Ruschkowski, Eick; Assmann, Thorsten
Abstract: The drastic insect decline has received increasing attention in scientific as well as in public media. Long‐term studies of insect diversity trends are still rare, even though such studies are highly important to assess extent, drivers and potential consequences of insect loss in ecosystems. To gain insights into carabid diversity trends of ancient and sustainably managed woodlands, we analysed data of carabid beetles from a trapping study that has been run for 24 years in an old nature reserve of Northern Germany, the Lüneburg Heath. We examined temporal changes in several diversity measures (e.g. biomass, species richness, functional diversity and phylogenetic diversity) and tested diverse species traits as predictor variables for species occurrence. In contrast to recently published long‐term studies of insect diversity, we did not observe a decline in biomass, but in species richness and phylogenetic diversity in carabids at our study site. Additionally, hibernation stage predicted the occurrence probability of carabids: Species hibernating as imagines or both imagines and larvae and breeding in spring showed strongest declines. We assume the detected trends to be the result of external effects such as climate change and the application of pesticides in the surrounding. Our results suggest that the drivers for the insect decline and the responses are multifaceted. This highlights the importance of long‐term studies with identification of the catches to, at best, species level to support the understanding of mechanisms driving changes in insect diversity and abundance. Abstract : We analysed data of carabid beetles from a 24‐year‐trapping study in a forest nature reserve in Northern Germany and examined temporal changes in biomass, species richness, functional diversity and phylogenetic diversity. We did not observe a decline in biomass, but in species richness and phylogenetic diversity in carabids at our study site. Hibernation stage predicted the occurrence probability of carabids: Species hibernating as imagines or both imagines and larvae and breeding in spring showed strongest declines.